Lipid and volatile profiles of Finnish oat batches of pure cultivars : Effect of storage on the volatile formation - Puganen, Anna (Elsevier, 2025)
Recent data showing the compositional variation and storage behavior among different oat batches for the purpose of food remains limited. Lipids of twenty oat flour samples of pure cultivars grown in Finland during 2019 were extracted and fractionated into neutral and polar-rich lipids. Flour was stored for nine months, and profiles of volatiles and tocols were analyzed to reveal oxidative stability. The lipid content was 5.9–8.9 g per 100 g of flour [DW] and consisted of 78.7 ± 2.5 % neutral and 21.3 ± 2.5 % polar lipids. Palmitic (16 %), oleic (36 %), and linoleic (39 %) acids were the most abundant fatty acids. Neutral lipids had more oleic and less linoleic and palmitic acids than polar lipids. The fresh samples correlated with tocols, pentanal, 2-pentylfuran, 2-heptanone, nonanal, 2-butanone, and heptanal, while stored samples were associated with 3-octen-2-one, 2-octenal, hexanal, and octanal. Lipid composition and oxidative stability are essential factors for selecting oat batches for food applications.